DEDICATED BREAST CANCER MANAGEMENT CENTRES WITH FACILITIES FOR FULL IMAGE-GUIDED ASSESSMENT AND IMAGE-GUIDED SURGERY IN THE DEVELOPING AREAS OF PAKISTAN - A LONG OVERDUE NECESSITY - Ahmad, Saeed; Ginawi, Alaa Eldin; Sabbagh, Samer (Journal of Ayub Medical College Abbottabad, 2015)
Background: Dedicated centres to manage breast cancers are important to combat this menace. An example of practice in the UK Hospitals is given with an attempt to explain reasons for an urgent need of dedicated breast cancer centres in developing areas of Pakistan. Methods: The rates of breast conservation, mastectomy, and immediate breast reconstruction are compared between a centre in the UK and a secondary radiotherapy facility in developing areas in Pakistan for 2011. Results: At Kettering General Hospital, 152 patients (71%) had breast conservation therapy including image-guided surgery, 45 (29%) had mastectomy and 15 (33.3%) had immediate breast reconstruction. All the 263 patients who had adjuvant therapy with surgery, has had mastectomy at the institute of radiotherapy and nuclear medicine (IRNUM) in Peshawar, and no patient had immediate reconstruction. Conclusion: The availability of mammogram in individual clinics inPeshawar, without the back up of dedicated breast cancer centre fails to materialize the dream of provision of whole spectrum of breast cancer care. Government and international donor organisations may need to be approached for investment in technology and training of personnel. Keywords: Mastectomy, Immediate Reconstruction, Breast Conservation Therapy (BCT)